2011
DOI: 10.1055/s-0031-1275526
|View full text |Cite
|
Sign up to set email alerts
|

New Challenges in the Diagnosis, Management, and Prevention of Central Venous Catheter-Related Infections

Abstract: Catheters are the leading source of bloodstream infections in critically ill patients. Because the clinical signs of infection are nonspecific, such infections are overly suspected, which results in unnecessary removal of catheters. A conservative approach might be attempted in mild infections, whereas catheters should always be removed in cases of severe sepsis or septic shock. Nowadays, comprehensive unit-based improvement programs are effective to reduce catheter-related bloodstream infections (CR-BSIs). Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 90 publications
(106 reference statements)
0
22
0
6
Order By: Relevance
“…However, this meta-analysis unmasked significant heterogeneity across study results, and the pooled CR-BSI rate in the control groups was unacceptably high in two studies (7.2% and 14%). When taking into account only the three studies with acceptable CR-BSI rates, chlorhexidine/silver/sulfadiazine-impregnated catheters failed to significantly decrease the CR-BSI rate (impregnated 8/614 vs. control 9/589 catheters; OR (random effect), 0.852; 95% CI, 0.2-3.6) [81]. …”
Section: Introductionmentioning
confidence: 99%
“…However, this meta-analysis unmasked significant heterogeneity across study results, and the pooled CR-BSI rate in the control groups was unacceptably high in two studies (7.2% and 14%). When taking into account only the three studies with acceptable CR-BSI rates, chlorhexidine/silver/sulfadiazine-impregnated catheters failed to significantly decrease the CR-BSI rate (impregnated 8/614 vs. control 9/589 catheters; OR (random effect), 0.852; 95% CI, 0.2-3.6) [81]. …”
Section: Introductionmentioning
confidence: 99%
“…entral venous catheters are routinely used to administer medication or fluids to patients admitted to oncology, nephrology, and intensive care units (2,47,52). Although these devices greatly improve patient health, their use is often associated with medical complications due to colonization by pathogenic microorganisms (38).…”
mentioning
confidence: 99%
“…This is in accordance with observations by Lloyd et al (48), who did not observe fibrin sheath formation on intravenous catheters within the first 15 to 30 min following insertion, and with those by Mehall et al (35), who showed that fibrin sheaths around implanted catheter favored bacterial attachment following bacteremia. Moreover, these results also support that although catheter colonization arising from a skin entry site at the time of insertion is the most frequent route of colonization, long-term implanted IVC infections result from breakthrough seeding from other sources via transient bacteremia (49). This explains why clinical studies on the prevention of IVC-associ- ated infections using catheters coated with Ag yielded disappointing results (19,50,51).…”
Section: Discussionmentioning
confidence: 58%